PERBANDINGAN BIAYA PELAKSANAAN PEKERJAAN DINDING MENGGUNAKAN BATA RINGAN DAN BATA MERAH PADA PERUMAHAN TYPE 36 - Ari Karya Agung Pambudi; Rasio Hepiyanto (Litbang Pemas - Universitas Islam Lamongan, 2019)
The wall is one of the non-structural elements contained in a building or house. Red brick is the main material that is often used and technological developments in the field of Civil Engineering continue to go hand in hand with the needs of the people who prioritize comfort, especially regarding their place of residence. Therefore, light brick is created so that it can lighten the structural load of a construction building, speed up the implementation, and minimize the remaining material that occurs during the wall installation process. This study aims to determine the comparison of the cost of carrying out the work of a pair of walls between the work of wall pairs using lightweight brick material with the work of wall pairs using red brick material. The object of this field study is the type 36 house construction project, the new beautiful Griya Suci housing, Jl. KH Syafi'I, Manyar, Gresik regency, East Java 61124. The study used a comparative descriptive study, which compares the costs between the implementation of a light brick wall worker and red brick. To get accurate data can be done by observation, interviews, documentation and through library books. Based on the results of this field study: (1) From the results of the study obtained the cost of materials for lightweight masonry is Rp. 92,134.- while for a pair of red brick walls Rp. 69.925.- (2) The wage cost of a lightweight brick wall pair is Rp. 40,300. While a red brick wall pair is 48,400. (3) Difference in the cost of a lightweight brick and red brick wage Rp. 14,109. red brick wall pair Rp. 22,209.-. From the regression relationship between time duration and cost, the equation Y = 8100 x + 7900 with R2 = 1 is obtained. This study can be concluded that the comparison of the work of installing light brick walls is cheaper than using red brick.